Facile synthesis of Ni-Doped ZnO nanostructures via laser-assisted chemical bath synthesis with high and durable photocatalytic activity - Zyoud, Samer H.; Ganesh, Vanga; Che Abdullah, Che Azurahanim; Yahia, Ibrahim S.; Zyoud, Ahed H.; Abdelkader, Atef F. I.; Daher, Malek G.; Nasor, Mohamed; Shahwan, Moyad; Zahran, Heba Y.; Abd El-Sadek, Mahmoud S.; Kamoun, Elbadawy A.; et al. (Multidisciplinary Digital Publishing Institute, 2023)
Pure and Ni-doped (1%, 2%, and 3%) nanostructures were synthesized using a novel laser-assisted chemical bath synthesis (LACBS) technique. For the first time, LACBS was used to create a doping solution utilizing a 7 W blue laser with a 444.4 nm wavelength and a continuous beam. The Ni-doping concentration was varied by changing the amount of Ni precursor added. All samples were analyzed using XRD, SEM, EDX, FTIR, UV–Vis, and photocatalysis tests for photodegradation under blue laser illumination. XRD was used to confirm that the tested ZnO had a hexagonal wurtzite structure. The crystallite size decreased as the Ni-doping concentration rose. EDX experiments were conducted to analyze the elemental characteristics of the pure and Ni-doped (1%, 2%, and 3%) nanostructures. The existence of nanoscale hexagonal structures was confirmed through SEM studies. The band gap values of the pure and Ni-doped ZnO nanostructures decreased as the doping concentration increased. FTIR studies were conducted to examine the functional groups of the pure and doped samples. The produced materials exhibited excellent photocatalytic performance toward the degradation of MB organic dye, an example of a pollutant found in wastewater.